Adipose Tissue Remodeling: Its Role in Energy Metabolism and Metabolic Disorders - Choe, Sung Sik; Huh, Jin Young; Hwang, In Jae; Kim, Jong In; Kim, Jae Bum (Frontiers in Endocrinology, 2016)
The adipose tissue is a central metabolic organ in the regulation of whole-body energy homeostasis. The white adipose tissue (WAT) functions as a key energy reservoir for other organs, whereas the brown adipose tissue (BAT) accumulates lipids for cold-induced adaptive thermogenesis. Adipose tissues secret various hormones, cytokines, and metabolites (termed as adipokines) that control systemic energy balance by regulating appetitive signals from the central nerve system as well as metabolic activity in peripheral tissues. In response to changes in the nutritional status, the adipose tissue undergoes dynamic remodeling, including quantitative and qualitative alterations in adipose tissue resident cells. A growing body of evidence indicates that adipose tissue remodeling in obesity is closely associated with adipose tissue function. Changes in the number and size of the adipocytes affect the microenvironment of expanded fat tissues, accompanied by alterations in adipokine secretion, adipocyte death, local hypoxia, and fatty acid fluxes. Concurrently, stromal vascular cells in the adipose tissue, including immune cells, are involved in numerous adaptive processes, such as dead adipocyte clearance, adipogenesis, and angiogenesis, all of which are dysregulated in obese adipose tissue remodeling. Chronic over-nutrition triggers uncontrolled inflammatory responses, leading to systemic low-grade inflammation and metabolic disorders, such as insulin resistance. This review will discuss current mechanistic understandings of adipose tissue remodeling processes in adaptive energy homeostasis and pathological remodeling of adipose tissue in connection with immune response.